Electrospun polycaprolactone scaffolds loaded with a 1,4-naphthoquinone derivative for anticancer therapy - Danilenko N. V. Nadezhda Viktorovna; Bolbasov E. N. Evgeny Nikolaevich; Khlebnikov A. I. Andrey Ivanovich; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Tverdokhlebov S. I. Sergei Ivanovich; Quinn M. T. Mark (2022, 2022)
Title screen